Dordt and South Africa. The nature and challenges for Reformed Church polity in South Africa - Coertzen, Pieter (Nederduitse Gereformeerde Teologiese Tydskrif, 2013)
Under the title Dordt and South Africa – the nature and challenges for Reformed Church Polity in South Africa this presentation starts by sketching the context in which the Church Order of Dordt was drawn up and what the role and meaning of the Church order was for the Reformed Churches in the Netherlands. Secondly attention is paid to the role of the Church Order of Dordt in the history of South Africa – given it’s context and meaning in the Netherlands. Given the background of the first two parts the presentation then goes on to identify new developments and challenges for Reformed Church Polity in South Africa such as the effect of the new SA Constitution that was accepted in 1994/1996; and the effect of guaranteed freedom of religion on matters like the debate between religions; the identity of the church and church unity.